Adult Colonic Intussusception due to a Lipoma Mimicking Carcinoma - Karkee, Dhan Vikram (Nepalese Medical Journal, 2018)
Adult colonic intussusceptions are rare and most of them are caused by malignant lesions. Presentation varies and preoperative diagnosis is unusual. We describe a case of 42 year gentleman with a colonic intussusception due to a lipoma. The lipoma was located in the descending colon and appeared like a carcinoma on colonoscopy. Though CT scan correctly diagnosed the entity intussusception and benign lipoma in this case, a formal bowel resection was performed because of suspicious colonoscopic features and high incidence of malignancy in the colonic intussusception. This case is unique, in the sense that, it mimicked carcinoma, it was on the left colon and it progressed to intussusception during hospital stay.